Data, information, and knowledge-driven manipulation between strategical planning and technical implementation for wireless sensor network construction. (November 2017) - Duan, Yucong; Shao, Lixu; Yang, Xiaoxian; Sun, Xiaobing; Zhou, Zhangbing; Yu, Lifeng
To provide guidance to and integrate directly with the information technology side implementation to achieve coherent data, information, and knowledge coordination and robust value-oriented adaptability for maximization of business profitability, we propose to leverage the ideology of service economics to achieve bidirectional computational bridging between business planning and technical implementation of ubiquitous services/XaaS in the application program interface economy for promoting the macro-service market, especially in global value chains. Enlightened by value-driven design, we propose a systemic formalization from value calculation to design quality measurement which binds the technical modification and variation on design artifacts with business value strategy through a framework of managed quality properties in a wireless sensor network–based service system creation process. In the process of building a service system, we use data, information, and knowledge flow to abstract various data, information, and knowledge manipulation and usage scenarios. We propose to improve system reliability and robustness by managing data and information reuse, redundancy as well as structure.